Effectiveness of tomato juice (Lycopersicum esculentum mill.) at 100% and 50% concentrations on discolorized teeth: Efektivitas jus buah tomat (Lycopersicum esculentum mill.) Konsentrasi 100% dan 50% pada gigi yang mengalami diskolorisasi - I Gusti Ketut Armiati; Made Mega Indah Purnamawati (Makassar Dental Journal PDGI Makassar, 2026)
Tooth discolouration due to coffee consumption is a common aesthetic problem. Chemical bleaching agents have been proven effective, but they can cause side effects such as tooth sensitivity and gum irritation, necessitating safer natural alternatives. Tomatoes (Lycopersicum esculentum Mill.) contain hydro-gen peroxide and peroxidase, which have the potential to be used as natural teeth whitening agents. This study evaluated the effectiveness of 100% and 50% tomato juice in whitening discoloured teeth. A laboratory experimental study with a pretest–posttest group design was conducted using 27 post-extraction teeth divided into three groups: 100% and 50% tomato juice, and sterile aquadest as a control. The samples were soaked for 3 hours, then the change in tooth colour (?E*ab) was measured with a spectrophotometer. Data analysis using paired t-tests and one-way Anova showed significant differences before and after treatment (p<0.05). The Tukey post hoc test showed that 100% tomato juice had the greatest whitening effect compared to 50% tomato juice and the control. It was concluded that 100% and 50% tomato juice concentrations were effective in whitening teeth discoloured by coffee, with the highest effective-ness at a concentration of 100%.